Genetic analysis of Respiratory Syncytial Virus strains circulating in children less than 5 years in Karachi-Pakistan - Miss Fatima Aziz; Dr Syed Asad Ali; Dr Syed Hani Abidi (International Journal of Infectious Diseases)
Background: Respiratory syncytial virus (RSV) is one of the leading causes of infant morbidity and mortality worldwide, especially in low- and middle-income countries, such as Pakistan, where the burden of RSV-associated morbidity and mortality is substantial. While few studies have explored the RSV epidemiology in different areas of Pakistan, very few have performed comprehensive genetic, phylogenetic, and phylodynamic analyses of RSV strains. This study presents a comprehensive genetic and phylodynamic analysis of RSV strains in children aged less than 5 years admitted to a tertiary care hospital in Karachi, Pakistan. Methods: Nasopharyngeal (swab) samples from 155 children with qPCR-confirmed RSV infection were used to perform RSV genotyping using PCR and sequencing-based strategy employing RSV glycoprotein (G) gene-specific primers. The RSVA and RSVB genotyping was performed using BLAST and Maximum-likelihood (ML) phylogenetic methods, while the relationship with other RSV strains was analyzed using ML phylogenetic cluster analysis. Furthermore, the time to the most common recent ancestor (tMRCA) and effective population size of RSV genotypes A and B were estimated using a Bayesian Markov Chain Monte Carlo (MCMC) analysis in BEAST software. Results: Out of 155, 98 sequences were found to be RSVA and 57 were found to be RSVB sequences. The tMRCA was estimated to be 2002 (1997–2006; upper-lower 95% HPD) for RSVA and 2005 (2002–2007; upper-lower 95% HPD) for RSVB gene sequences. RSVA sequences formed two clusters (15 sequences clustered with the NA1 genotype and 83 formed a unique cluster), whereas RSVB formed three clusters (two sequences were clustered with the BA12 genotype, 24 sequences clustered with the BA9 genotype, and 31 sequences formed a unique cluster) on the ML phylogenetic analysis. Conclusions: Our results suggest that the RSVA and RSVB strains from Pakistan exhibit genotype diversity evident from the key findings regarding the subtype distribution of sequences, estimated common ancestry timelines, and clustering patterns for RSVA and RSVB glycoprotein gene sequences. This could be an essential baseline data for Southeast Asia for the early detection of newly emergent RSV variants and the development of further effective regimen against RSV.